Publication performance and trends in psychological capital research: a bibliometric analysis - Van-Chien Pham; Wing-Keung Wong; Xuan Thi Bui (Journal of Trade Science)
Purpose – This research aims to provide a comprehensive understanding of the evolution and trends in psychological capital (PsyCap) research and related issues. Design/methodology/approach – This research uses bibliometric analysis. A total of 2,244 journal articles were extracted from the Scopus database using relevant keywords, covering the period from 1997 to 2023. The data analysis was conducted utilizing VOSviewer software, Microsoft Excel, and an online text analysis tool. Findings – There is a rapid rise in the quantity of PsyCap publications, especially from 2017, with significant contribution of research from Chinese scholars with 577 articles in the period 2019–2023. The antecedents of PsyCap have a stagnation of leadership-related topics and increased focus on social support and perceived organizational support. The attention has been specifically directed toward well-being and mental health, with special emphasis on work engagement, job satisfaction, and job performance. Research limitations/implications – The exclusion of certain publications in this research may overlook emerging trends. Thus, future research endeavors should adopt a multifaceted approach that combines bibliometric analysis with qualitative and quantitative methods to glean comprehensive insights into PsyCap research. Originality/value – PsyCap research is growing rapidly, with more publications in the last three years than in all the previous years combined. This study, updating data until the end of 2023, provides the most up-to-date insights on research trends in PsyCap to aid scholars in discerning suitable avenues for their research endeavors.